2019
DOI: 10.1093/ejcts/ezz279
|View full text |Cite
|
Sign up to set email alerts
|

Non-intubated spontaneous ventilation in video-assisted thoracoscopic surgery: a meta-analysis

Abstract: It remains unclear whether non-intubated video-assisted thoracoscopic surgery (VATS) is comparable or advantageous compared with conventional intubated VATS. Thus, we systematically assessed the feasibility and safety of non-intubated VATS compared with intubated VATS perioperatively for the treatment of different thoracic diseases. An extensive search of literature databases was conducted. Perioperative outcomes were compared between 2 types of operations. The time trend of the overall results was evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 55 publications
0
39
0
1
Order By: Relevance
“…However, the evidence supporting non-intubated VATS as the preferred approach for lung surgery is still limited. Previous meta-analyses reported that non-intubated procedure attenuated the in ammatory response and stress, followed by fewer postoperative complications as compared with the intubated VATS [15,16]. Moreover, the indications for VATS could be extended by this less-invasive procedure.…”
Section: Discussionmentioning
confidence: 97%
“…However, the evidence supporting non-intubated VATS as the preferred approach for lung surgery is still limited. Previous meta-analyses reported that non-intubated procedure attenuated the in ammatory response and stress, followed by fewer postoperative complications as compared with the intubated VATS [15,16]. Moreover, the indications for VATS could be extended by this less-invasive procedure.…”
Section: Discussionmentioning
confidence: 97%
“…However, the evidence supporting non-intubated VATS as the preferred approach for lung surgery is still limited. Previous meta-analyses show that non-intubated procedures could attenuate surgery-related stress responses and decrease postoperative complications compared to intubated surgery [15,16]. Moreover, for patients who are considered as high-risk under intubated general anesthesia due to their compromised lung function, non-intubated procedure could be considered [17].…”
Section: Discussionmentioning
confidence: 99%
“…Inzwischen gibt es erste Metaanalysen, die einen Vorteil der Non-intubated VATS unter Erhalt der Spontanatmung bez. der postoperativen Komplikationsraten, der postoperativen Nüchternheitszeiten und kürzeren Narkose-und Operationszeiten im Vergleich zur konventionellen VATS in Allgemeinanästhesie zeigen [8,9] Bezüglich der präoperativen Patientenauswahl lassen sich in der Literatur einige Empfehlungen finden, die sich größtenteils decken und überschneiden [10 -12] Daten oder Empfehlungen zur intraoperativen Sedierung lassen sich nur sporadisch aus der Literatur entnehmen. Aufgrund der ultrakurzen kontextsensitiven Halbwertszeit von 4 min scheint sich Remifentanil als eines der bevorzugten Medikamente zur Sedierung während Thorakoskopien unter Erhalt der Spontanatmung zu bewähren [4].…”
Section: Studiendesignunclassified